PENERAPAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP PENERIMAAN KRS ONLINE - Fatmasari, Fatmasari; Ariandi, Muhammad (JURNAL ILMIAH MATRIK, 2014)
This studywas conducted to determine the prediction confidenceas well as computer science students to analyze the utilization of facilities krs line with the model approach techonology acceptance model (TAM), where the variables analyzed were Perceived ease of use(PEU), Perceived us efulness(PU), Behavioral intention of use(bitu) Where the respondent is a computer science student of Bina Darma University Palembang. In the sampling is done with a simple random sampling technique. Testing phase is done with test validity, Reliability of test and correlation tes tto variable PEU and PU. In the discriminant analysis was conducted to determine the level of student confidence predictions. Processing data Use SPSS software as tools. The expected resultis of significan tindependent variable test samples to determine the level of student confidence predictions.